Efeito do Triterpeno 3β, 6β, 16β , trihidroxilup-20(29)-eno nas convul-sões induzidas por pentilenotretazol: papel da Na+, K+ ATPase - Della Pace, Iuri Domingues (2013)
Epilepsy is a syndrome characterized by spontaneous recurrent seizures, result of paroxys-mal discharges , excessive or synchronous a neural population . Despite the good prognosis, the high number of patients with epilepsy who have seizures refractory to medication, reflects the lack of a bet-ter understanding of excitotoxic disorders characteristic of this disease. Thus, it becomes important to understand the mechanisms for induction and maintenance of seizures as well, the search for new antiepileptic compounds that may prevent the development of this pathology. As nociception and epi-lepsy have mechanisms in common and several anticonvulsant drugs are used in treatment of pain , we investigated the effect of triterpene 3β , 6β , 16β Trihidroxilup -20 ( 29) -ene (TTHL), a compound with antinociceptive properties in convulsions induced by pentylenetetrazol (PTZ). The TTHL admin-istration ( 30 mg / kg , po) increased the latency to the first myoclonic seizures and tonic- clonic sei-zure and decreased the duration of generalized seizures induced by PTZ . In addition , the administra-tion of TTHL reduced lipid peroxidation and protein carbonylation , as well as protected from inhibition of glutamate uptake and activity of the Na+, K+-ATPase (α1and α2/α3 subunits ) caused by PTZ . Alt-hough the TTHL showed no antioxidant activity per se and not alter the binding of [ 3H ] flunitrazepam to the site of the GABAA receptor bezodiazepínico , this protected compound of convulsions and inhi-bition of Na+, K+-ATPase activity induced by ouabain . These results suggest that the anticonvulsant action is due TTHL s maintenance of Na+, K+-ATPase . In fact , the experiments performed in the cer-ebral cortex in vitro showed that PTZ ( 10 mM ) reduced the activity of Na+, K+-ATPase and that prein-cubation with TTHL ( 10 mM ) protected from this inhibition.Thus , these data indicate that the protec-tion exerted by TTHL this seizure model is not related to antioxidant activity or GABAergic activity . However, these results demonstrate that effective protection of Na+, K+-ATPase activity induced by this compound protects against oxidative and excitotoxic damage induced by PTZ .